2022
DOI: 10.3390/pathogens11040444
|View full text |Cite
|
Sign up to set email alerts
|

Increased Indoleamine 2,3-Dioxygenase 1 (IDO-1) Activity and Inflammatory Responses during Chikungunya Virus Infection

Abstract: Chikungunya virus (CHIKV) infection causes intense cytokine/chemokine inflammatory responses and debilitating joint pain. Indoleamine2,3–dioxygenase 1 (IDO-1) is an enzyme that initiates the tryptophan degradation that is important in initial host innate immune defense against infectious pathogens. Besides that, IDO-1 activation acts as a regulatory mechanism to prevent overactive host immune responses. In this study, we evaluated IDO-1 activity and cytokine/chemokine patterns in CHIKV patients. Higher IDO-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…Most of the top cytokines and transcriptional regulators ( Figure 4 ) are well described in the CHIKV literature, and as expected are dominated by interferon (IFN) and Th1 responses ( 1 , 15 , 40 , 41 , 54 , 60 , 63 66 ). Perhaps surprising is the absence of CCL2/CCR2 as an USR, even though CCL2 is a highly significant DEG, and is well described for CHIKV infections ( 45 , 55 , 67 ).…”
Section: Resultssupporting
confidence: 63%
“…Most of the top cytokines and transcriptional regulators ( Figure 4 ) are well described in the CHIKV literature, and as expected are dominated by interferon (IFN) and Th1 responses ( 1 , 15 , 40 , 41 , 54 , 60 , 63 66 ). Perhaps surprising is the absence of CCL2/CCR2 as an USR, even though CCL2 is a highly significant DEG, and is well described for CHIKV infections ( 45 , 55 , 67 ).…”
Section: Resultssupporting
confidence: 63%
“…Several studies have reported increased levels of chemokines such as eotaxin, MIP-1α and MIP-1β in both acute and chronic phase of CHIKD and often associated with disease severity. 19 , 20 , 23 Previous studies have associated chemokines such as eotaxin with neurological complications in CHIKD. 20 However, another study by Chow and colleagues reported that patients who fully recovered had high levels of eotaxin.…”
Section: Discussionmentioning
confidence: 99%
“…Other chemokines such as IP-10, MIG and MCP-1 were elevated in the acute phase, as mentioned in a few other studies. 10 , 23 Molecules such as MCP-1 have been reported to regulate CHIKV viral load along with IP-10 24 and along with MIG, found to be associated with persistent arthralgia 10 and neurological complications. 20 , 25 Of interest in the present study was RANTES, which was found to be downregulated in acute and became further significantly downregulated in the convalescent phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the tissue remains inflamed for a long time, inflammation can also damage healthy tissue and induce secondary repair, including fibrosis. Proinflammatory cytokines, such as interferon gamma, and other inflammatory signaling molecules, including the lipid mediator prostaglandin E2 and lipopolysaccharide pathogen particles, induce the overexpression of IDO1 (Baumgartner et al, 2019;Alves de Souza et al, 2022). The activation of IDO1 in response to these inflammatory factors induces immune tolerance and eventually controls hyperinflammation (Zhai et al, 2020).…”
Section: Inflammationmentioning
confidence: 99%